2019
DOI: 10.1128/aac.02204-18
|View full text |Cite
|
Sign up to set email alerts
|

Rufomycin Targets ClpC1 Proteolysis in Mycobacterium tuberculosis and M. abscessus

Abstract: ClpC1 is an emerging new target for the treatment of Mycobacterium tuberculosis infections, and several cyclic peptides (ecumicin, cyclomarin A, and lassomycin) are known to act on this target. This study identified another group of peptides, the rufomycins (RUFs), as bactericidal to M. tuberculosis through the inhibition of ClpC1 and subsequent modulation of protein degradation of intracellular proteins. Rufomycin I (RUFI) was found to be a potent and selective lead compound for both M. tuberculosis (MIC, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 85 publications
(143 citation statements)
references
References 56 publications
6
137
0
Order By: Relevance
“…Moreover, both ecumicin and lassomycin have been tested for activity against susceptible, MDR and XDR clinical M tuberculosis isolates, with MICs of 0.26 to 1.0, 0.5, and 0.5 to 1.0 μg/mL obtained for ecumicin, respectively . Anti‐TB activity analyses of ecumicin, rufomycin I, and cyclomarin A on M tuberculosis H37Rv strain, virulent strains, and drug‐resistant strains have shown that rufomycin I, cyclomarin A, and ecumicin are more active than capreomycin and the first‐line TB‐drug isoniazid . For lassomycin, the MICs against susceptible and drug‐resistant M tuberculosis strains were found to be between 0.78 and 3.1 μg/mL .…”
Section: Quest For Novel Drugs: Proteins and Peptidesmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, both ecumicin and lassomycin have been tested for activity against susceptible, MDR and XDR clinical M tuberculosis isolates, with MICs of 0.26 to 1.0, 0.5, and 0.5 to 1.0 μg/mL obtained for ecumicin, respectively . Anti‐TB activity analyses of ecumicin, rufomycin I, and cyclomarin A on M tuberculosis H37Rv strain, virulent strains, and drug‐resistant strains have shown that rufomycin I, cyclomarin A, and ecumicin are more active than capreomycin and the first‐line TB‐drug isoniazid . For lassomycin, the MICs against susceptible and drug‐resistant M tuberculosis strains were found to be between 0.78 and 3.1 μg/mL .…”
Section: Quest For Novel Drugs: Proteins and Peptidesmentioning
confidence: 99%
“…Studies on the mechanism of action of rufomycin, ecumicin, cyclomarin, and lassomycin identified the ClpC1 ATPase complex as the drug target of these peptides. Ecumicin and lassomycin act through enhancing ATPase activity while blocking ClpC1p1p2‐catalysed proteolysis while cyclomarin A does not affect the ATPase activity and increasing proteolysis . The in vivo study carried out by Gao and colleagues found that 12 doses of 20 or 32 mg/kg ecumicin were enough to completely inhibit the growth of the pathogens from the lungs of mice infected by M tuberculosis Erdman strain .…”
Section: Quest For Novel Drugs: Proteins and Peptidesmentioning
confidence: 99%
See 3 more Smart Citations